Trends and Outcomes of the Management of Common Bile Duct Stones at KIST Medical College Teaching Hospital - Bohara, Tanka Prasad; Joshi, Mukund Raj; Dangol, Ellina; Singh, Akanand; Bhatta, Ashish (Journal of Society of Surgeons of Nepal, 2024)
Introduction: Common bile duct (CBD) stones are found in 10% to 15% of patient having cholelithiasis. Various surgical methods including endoscopic, laparoscopic and open surgical techniques are practiced but there is no consensus on the management. This cross-sectional study aims to analyze the demographics and trends un management of CBD stones at KIST Medical College. Methods: Patient undergoing CBD stone management from 15 June 2021 to 31 December 2023 were included in the study. Different treatment methods applied and outcomes were analyzed. Results: Fifty-one patients were included in the study with 18 (25.3 %) males and 33 (64.7%) females. Abdominal pain was the most common symptom. Laparoscopic cholecystectomy(LC) with intraoperative(io)-ERCP was done in 30 (58.8%) patients, while LC + Laparoscopic CBD exploration(LCBDE) was done in 11 (21.6 %) and Endoscopic Retrograde Cholangiopancreatography(ERCP) only was done in 10 (19.6%) patients. The significant difference was observed in the length of hospital stay [5.03 ± 2.13 vs 6.36 ± 2.29, p=0.046] and the number of days the drain was kept [2.20 ±0.45 vs 4 ± 1.90, p=0.037] both favoring LC + io-ERCP group. Stone clearance, post-operative complications and operative time were comparable between the two groups. Conclusion: Single-stage management of cholelithiasis and choledocholithiasis is feasible at our center. Both LC with io-ERCP and LC + LCBDE can be performed selectively with acceptable and comparable outcomes.